KEPASTIAN HUKUM DALAM PENEGAKKAN HUKUM PERPAJAKAN - Agus Iskandar (PRANATA HUKUM, 2019)
ABSTRAK Tax amnesty in the form of tax debt relief along with sanctions creates legal problems. The problem is how to enforce the law on the principle of legality in the legal system of taxation in Indonesia. This study uses a normative juridical approach, therefore the main data used is secondary data in the form of legislative regulations - data analysis invitations carried out in qualitative analysis. Based on the results of the study, that legal certainty in law enforcement by looking at the inaccuracies of regulations concerning the substance and form of legislation - invitation will weaken the principle of legality. From the experience of tax amnesty implementation, it turns out that tax amnesty does not necessarily increase state revenues, nor does tax amnesty automatically increase investment. As a suggestion, tax amnesty as an incentive needs to get policy support from other sectors so as to create the expected investment climate.